Holocene climate variability in north-eastern Italy: potential influence of the NAO and solar activity recorded by speleothem data - D. Scholz; S. Frisia; A. Borsato; C. Spötl; J. Fohlmeister; M. Mudelsee; R. Miorandi; A. Mangini (Climate of the Past, 2012)
Here we present high-resolution stable isotope and lamina thickness profiles as well as radiocarbon data for the Holocene stalagmite ER 76 from Grotta di Ernesto (north-eastern Italy), which was dated by combined U-series dating and lamina counting. ER 76 grew between 8 ka (thousands of years before 2000 AD) and today, with a hiatus from 2.6 to 0.4 ka. Data from nine meteorological stations in Trentino show a significant influence of the North Atlantic Oscillation (NAO) on winter temperature and precipitation in the cave region. Spectral analysis of the stable isotope signals of ER 76 reveals significant peaks at periods of 110, 60–70, 40–50, 32–37 and around 25 a. Except for the cycle between 32 and 37 a all periodicities have corresponding peaks in power spectra of solar variability, and the 25-a cycle may correspond to NAO variability. This suggests that climate variability in northern Italy was influenced by both solar activity and the NAO during the Holocene. Six periods of warm winter climate in the cave region were identified. These are centred at 7.9, 7.4, 6.5, 5.5, 4.9 and 3.7 ka, and their duration ranges from 100 to 400 a. The two oldest warm phases coincide with the deposition of sapropel S1 in the Mediterranean Sea indicating that the climate in the cave region was influenced by this prominent pluvial phase in the Mediterranean area. For the younger warm phases it is difficult to establish a supra-regional climate pattern, and some of them may, thus, reflect regional climate variability. This highlights the complexity of regional and supra-regional scale Holocene climate patterns.